An Analysis of the Impact of Child-Friendly School Culture Implementation on Students’ Collaboration Skills at West Nusa Tenggara, Indonesia - Ni Wayan Asri Udayani; Vira Sasmita; Baiq Chunafa Diza Farhana; Lalu Sumardi; Dadi Setiadi (Indonesian Journal of Educational Innovation, 2025)
Schools are increasingly expected to create learning environments that support not only academic achievement but also students’ social and collaborative skills. This study analyzes the impact of implementing the Child-Friendly School (CFS) culture on elementary students’ collaboration skills at SDN 5 Cakranegara, Mataram City, West Nusa Tenggara, Indonesia. The study employed a qualitative case-study design. Data were collected through in-depth interviews, observations, and documentation involving the principal, teachers, students, and parents. The data were analyzed using Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that implementing the CFS culture positively impacts students’ collaboration skills by fostering an inclusive, safe, and participatory school environment. Routine activities, positive discipline practices, differentiated instruction, inclusive play settings, and parental involvement enhance students’ cooperation, communication, empathy, and mutual respect. However, several challenges remain, including limitations in school facilities and the persistence of competitive learning norms. In conclusion, the implementation of a Child-Friendly School culture effectively supports the development of students’ collaboration skills and social-emotional competencies. This study implies that child-friendly education should be strengthened through continuous evaluation, collaborative learning strategies, and sustainable school–parent partnerships to maintain inclusive and collaborative learning environments in elementary schools